1992
DOI: 10.1111/j.1748-1716.1992.tb09407.x
|View full text |Cite
|
Sign up to set email alerts
|

Vasoconstrictor reactions in spontaneously hypertensive rats versus Wistar Kyoto can be increased or decreased depending on the conditions of perfusion

Abstract: The reactions of resistance vessels in SHR and WKY hindquarters were compared during saline or blood perfusion. During saline constant-flow perfusion at all initial pressures (80-200 mmHg) sympathetic vasoconstrictor effects were greater in SHR than those in WKY. During perfusion at constant and equal pressure vasoconstrictor responses were greater in SHR vs. WKY only at high pressure--200 mmHg. On the other hand, under constant pressure conditions at lower pressures (80 and 120 mmHg) sympathetic stimulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…An opposite relationship was observed at constant pressure perfusion: the vasoconstrictor response to noradrenaline being more prominent in the WKY vessel. These data are in agreement with earlier results (Rodionov et al 1992) obtained on hindquarters of SHR and WKY.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…An opposite relationship was observed at constant pressure perfusion: the vasoconstrictor response to noradrenaline being more prominent in the WKY vessel. These data are in agreement with earlier results (Rodionov et al 1992) obtained on hindquarters of SHR and WKY.…”
Section: Discussionsupporting
confidence: 94%
“…At high values of wall tension the difference in the response to extrinsic stimulation should be determined mainly by the media thickness: the greater the media thickness the greater the narrowing of the lumen. Actually, at high constant perfusion pressure (200 mmHg) the ef®ciency of vasoconstrictor stimulation in SHR became greater than in WKY (Rodionov et al 1992). Results of the experiments with constant¯ow perfusion support this point of view.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…It was shown that the myogenic response ampli®es the vasoconstriction induced by extrinsic stimulation (Meininger & Trzeciakowski 1988, Meininger & Faber 1991. Recently we have studied this phenomenon in perfused vessels from SHR and WKY rats (Rodionov et al 1992, Machkov et al 1997. In accordance with others (Folkow et al 1970, Cassis et al 1985, in these experiments vasoconstriction induced by noradrenaline or nerve stimulation under constant±¯ow perfusion in SHR was greater compared to WKY.…”
supporting
confidence: 78%
“…In contrast to the above‐quoted data it was shown that under constant pressure perfusion at a moderate pressure level, vasoconstrictor responses in SHR are weaker than those of WKYR (Rodionov et al ., 1992). An analysis of these phenomena is expedient on the entire organic vasculature where vessels with a different order of branching exhibit different reactivity to vasoconstrictor agents and to changes in intraluminal pressure (Maarshall, 1982; Maspers, Bjomberg, Grand & Mellander, 1990).…”
Section: Introductionmentioning
confidence: 83%